KERAJINAN MACRAME: SEBAGAI GERAKAN WOMEN’S EMPOWERMENT BASED CREATIVE ECONOMIC DALAM UPAYA PENGEMBANGAN PARIWISATA - Novyandra Ilham Bahtera; Laila Hayati; Vindi Kaldina (Jurnal Abdi Insani, 2023)
The increase in the number of tourist destinations on Bangka Island must be supported by sufficient tourism accommodations, one of which is distinctive products or souvenirs. The process of tourism development through souvenir production in the Bangka Belitung Islands Province needs to harness the potential of local community groups, one of which is through a program of women's economic empowerment based on creativity. One of the handicrafts worthy of being used as a souvenir is macramé craftsmanship. This program was conducted within the framework of community service in Kace Timur Village, Bangka Regency. Using a descriptive qualitative approach, this article aims to describe the process, results, and impact of women's empowerment through macramé craft training. The activities were divided into several stages, including preparation, socialization, training, and post-training evaluation. The output of the training includes keychains and walldecor made from macramé. The participants' enthusiasm was quite high in both the socialization and training stages, with almost all participants successfully producing macramé crafts. There were 33 keychains and 26 walldecors produced by participants from Kace Timur Village, Bangka Regency. The participants gained information and skills that can serve as the basis for the macramé craft production process, including knowledge, information on materials and equipment, pricing and cost calculations, as well as product packaging. In the future, it is hoped that through macramé craftsmanship, women, especially in Kace Timur Village, can improve their family's economy while also making a positive contribution to the development of tourism in Bangka Belitung.